Revealing the meaning in the Qur’anic discourse in the light of prose theory: stylistic approach - Azeb, Abderrahim (Journal of Human Sciences, 2021)
The arabic critical heritage had seen the emergence of the prose theory and it transposed relation with the Ijaz Quranic’s linguistic.a prose can be defined by the homogeneity between the word and the meaning, and among the innovative researches that has treated the thematic and textual polyphony through the prose’s paradigm and it several contexts Abou oubaida el mouthana in his book « Métaphor of  the Quran » also El faraa in his book « the meanings of the Quran » both has demonstrated that El Ijaz of Quran appears in his prosodic code while El jahed has noted in his book « prose of the Quran  » through his text or form.In addition, it is necessary that this thesis and research has to be started with vision of Abdelkader El jorjani in his own books « the evidences of El Ijaz » and «  the secrets of the rhetoric » while agreeing that the prose ,the rhyme and the rhythm are related into the same grammatical filed which needs munitive analysis and a dismantling very exacte .